Resurjensi Serangga Hama Karena Perubahan Fisiologi Tanaman dan Serangga Sasaran Setelah Aplikasi Insektisida - Yuni Ratna; Y. Andi Trisyono; Kasumbogo Untung; Didik Indradewa (Jurnal Perlindungan Tanaman Indonesia, 2009)
The use of insecticides at sub-lethal dosage may induce insect resurgence. Factors contributing the insect resurgence include mortality of natural enemies, mass migration, improvement in plant nutrition, or increase in insect reproductive capacity which works individually or in combinations. This article provides a comprehensive review from recent publications, particularly those dealing with the impact of insecticide applications on plant nutrition and insect reproduction, and function to upgrade our knowledge since most publications in Indonesia were made in the 1980s. The insecticides together with its metabolites and conjugates could function as plant growth regulators, increase absorption, improve the nutritional content, influence the biochemical and ultrastructural aspects of the plant, or protect the plant from stresses. An increase in the nutritional value of the plant would increase feeding rate, fecundity, and longevity of the insects. Furthermore, insecticides could also directly stimulate the reproductive capacity of the insect. All of these impacts might end up in increasing the population of insect after application of certain insecticides. Research findings related to the elucidation on the mechanism underlying the phenomenon of resurgence could be used in considering the registration of new insecticides or extension of the existing insecticides.